[Rezension von: Baldus, Bernd, Origins of inequality in human societies] - Schwinn, Thomas (de Gruyter, 2020)
Rezension von: Baldus, Bern, Origins of inequality in human societies. New York/London: Routledge 2017, 250 S., gb., 136,45 € (kt. 50,49 €)